Evaluation of Fim Performance under Merger and Acquisition Effect: An Integrated LOPCOW-PIV Approach - Sudipta Dey; Gautam Mitra; Sanjib Biswas; Dragan Pamucar (Decision Making: Applications in Management and Engineering, 2025)
Merger and Acquisition (MA) is one of the critical strategic decisions for the firms that impact the existence and growth of the organizations. The present paper undertakes the context of MA and aims to compare performance of some of the recent acquirers using fundamental financial ratios and market indicators. The study period spans over four consecutive financial years (FY 2019-20 to FY 2022-23). To carry out a comprehensive evaluation of firm performance, the current work uses a multi-criteria decision-making (MCDM) framework of LOPCOW (Logarithmic Percentage Change-driven Objective Weighting) and PIV (Proximity Index Value) methods. To aggregate the year wise rankings of the firms, Borda Count and Rank Index Method (RIM) is used. It is observed that ROE (C1), Net Profit Margin (C4) and EPS (C9) obtained the highest weights over the study period. On aggregate, we find that Infosys (A4), HUL (A3) and ITC (A1) show top performance while Vodafone (A11), PVR Inox (A9) and IDFC First Bank (A13) remain in the bottom bracket. The comparative analysis with other MCDM models reveals that the ranking results are consistent while the outcome of the sensitivity analysis reflects the stability. The present work provides a new perspective to the investors, policy makers and analysts